Diagnostic Utility of Superb Microvascular Imaging and Power Doppler Ultrasonography for Visualizing Enriched Microvascular Flow in Patients With Carpal Tunnel Syndrome - Endo, Takeshi; Matsui, Yuichiro; Kawamura, Daisuke; Urita, Atsushi; Momma, Daisuke; Ota, Mitsutoshi; Shibayama, Hiroki; Iwai, Takahito; Nishida, Mutsumi; Iwasaki, Norimasa (Frontiers in Neurology, 2022)
Recent studies suggest that blood flow changes in the median nerve may help confirm a diagnosis of carpal tunnel syndrome (CTS). Herein, we examined the utility of superb microvascular imaging (SMI), a new ultrasonographic (US) technique for visualizing microvascular flow, for detecting blood flow differences between CTS patients and healthy controls. We performed a retrospective analysis of 28 hands with suspected CTS. Patients received both nerve conduction and US examinations. Ten healthy volunteers were enrolled as the control group. The nerve compression ratio and the blood flow signal area were quantified using color Doppler US (CDUS), power Doppler US (PDUS), and SMI. Correlation analyses between the blood flow signal area, the compound muscle action potential of the thenar muscle, and the nerve compression ratio were performed. As a result, the mean nerve compression ratio was found to be significantly higher in the CTS group. There were no differences in the blood flow signal area between the groups using CDUS, while PDUS and SMI showed higher blood flow signals in the CTS group. The blood flow signal area measured by SMI had stronger correlations with the compound muscle action potential amplitude and the nerve compression ratio than those for PDUS. The diagnostic utility of SMI was equivalent to PDUS, but superior to conventional CDUS. Nevertheless, the blood flow signal by SMI was more strongly correlated with the electrophysiological severity and compression ratio than for PDUS. Use of SMI in future studies may help clarify the underlying mechanisms of blood flow changes in CTS.